Peculiarities of engineering and geological surveys when inspecting the historical building of Kharkiv - Aleksandrovych, Vadym; Havryliuk, Olha; Sukhov, Valeriy (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2021)
Formulation of the problem. The large volume of historic buildings that require major repairs, reconstruction and adaptation to modern use dictates the need to move to faster and more reliable technologies of architectural monuments restoration. In this regard, there is a need for a complex approach during the restoration work. The purpose of the article is to investigate the difficulty of obtaining the correct conclusions about the geological conditions of the building placement as a result of previously unqualified repair works on the example of engineering-geological surveys during the reconstruction of a historic building. Materials and methods. To achieve the goal, the analysis of engineering-geological conditions of the soil base of the building, visual inspection of the building, soil sampling from the pits in the basement of the survey object, as well as determining the physical-mechanical characteristics of the soil have been done. An analytical comparison of these data was performed to understand the constructive solution of the building foundations and engineering-geological conditions of their support. Results. During the working process, the lack of design and executive documentation for the building, as well as unqualified interference in its structure, was revealed. Therefore, one of the key issues was to determine the actual structure of the foundation, as well as the type and condition of its soil base. As a result of a complex analysis of the structural scheme of the underground part of the building, it was established that the basement was equipped after the construction of the building. To determine the structure, depth and condition of the foundation, pits were laid from the frontal and back walls of the building facade, which is adjacent to the site. During the laboratory studies of the soils, physical-mechanical characteristics were obtained for calculating building structures. Based on the data obtained, recommendations were issued for the further reconstruction of a non-residential building of the historical development of the city. Scientific novelty and practical significance. The necessity to research the actual technical state of building structures of a historical building is substantiated to assess the possibility of further reliable and safe operation according to its direct functional purpose, with the development of technical solutions and recommendations for further reconstruction of the building according to the needs of the customer, and ensuring its further uninterrupted and safe ope-ration. The practical application of the proposed results has been substantiated - the need for a complex approach during the restoration work for the further reconstruction of a non-residential building of the historical buildings of the city has been confirmed.